2002
DOI: 10.1007/s00439-002-0874-4
|View full text |Cite
|
Sign up to set email alerts
|

Testing hypotheses of language replacement in the Caucasus: evidence from the Y-chromosome

Abstract: A previous analysis of mtDNA variation in the Caucasus found that Indo-European-speaking Armenians and Turkic-speaking Azerbaijanians were more closely related genetically to other Caucasus populations (who speak Caucasian languages) than to other Indo-European or Turkic groups, respectively. Armenian and Azerbaijanian therefore represent language replacements, possibly via elite dominance involving primarily male migrants, in which case genetic relationships of Armenians and Azerbaijanians based on the Y-chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
39
0
3

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 17 publications
3
39
0
3
Order By: Relevance
“…Subsequent studies using diverse scales and methodologies have found variable degrees of association between linguistic and genetic classifications [17-22]. Some typical examples of exceptions are populations with language replacement [23-26] or recent admixture between divergent populations [27,28]. However, human genetic and linguistic diversity have been proposed to be generally correlated, either through a direct link, whereby linguistic and genetic affiliations reflect the same past population processes, or an indirect one, where the evolution of the two types of diversity is independent but conditioned by the same geographic factors [29].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies using diverse scales and methodologies have found variable degrees of association between linguistic and genetic classifications [17-22]. Some typical examples of exceptions are populations with language replacement [23-26] or recent admixture between divergent populations [27,28]. However, human genetic and linguistic diversity have been proposed to be generally correlated, either through a direct link, whereby linguistic and genetic affiliations reflect the same past population processes, or an indirect one, where the evolution of the two types of diversity is independent but conditioned by the same geographic factors [29].…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have used mitochondrial d-loop data and Y-chromosome data to investigate genetic and linguistic correspondence in various world regions [15], [16], [20], [77][81], but these data are comparatively uninformative. The Y-chromosome data typically contain only a few loci, and the mitochondrial d-loop data are plagued by homoplasy, which confounds the construction of genetic classifications and limits the accuracy of genetic distance estimation [82].…”
Section: Discussionmentioning
confidence: 99%
“…Am J Phys Anthropol 137: [41][42][43][44][45][46][47]2008. Previous studies have shown that Y-SNP haplogroups form different landscapes in terms of haplogroup composition and their frequencies in Europe, the Volga-Ural region and the Caucasus (Rosser et al, 2000;Semino et al, 2000;Nasidze et al, 2003Nasidze et al, , 2004. The European part of Russia is situated at a critical juncture between these regions, particularly with respect to the most informative haplogroups that vary across Europe: R1a1-M17, I-M170, and N3-TAT (Rosser et al, 2000).…”
mentioning
confidence: 99%
“…In this study, we present analyses of Y-SNP haplogroup and Y-STR haplotype variation in 12 groups from the European part of Russia. These new genetic data are combined with previously-published data on Y-SNP variation in the rest of Europe, the Volga-Ural region, the Caucasus and the Near East (Lahermo et al, 1999;Rosser et al, 2000;Semino et al, 2000;Wells et al, 2001;Passarino et al, 2002;Malyarchuk et al, 2004;Nasidze et al, 2003Nasidze et al, , 2004Kharkov et al, 2005) to address the following questions: (1) What are the genetic relationships of the Russian groups with respect to each other and other European, Uralic, Caucasian, and Near Eastern populations? and (2) How does the west European Y-SNP haplogroup landscape change over the European part of Russia towards the Volga-Ural region?…”
mentioning
confidence: 99%